Analisis Kepemimpinan, Lingkungan Kerja, dan Budaya Organisasi terhadap Kinerja Pegawai pada Sekretariat Daerah Kabupaten Bogor dengan Motivasi sebagai Variabel Moderating - Qoriatul Adawiyah; Hery Margono (Jurnal Syntax Admiration, 2024)
This study aims to determine how the influence of Leadership, Work Environment and Organizational Culture on Employee Performance at the Regional Secretariat of Bogor Regency with Motivation as a Moderating Variable. The research focuses on human resource management with quantitative methods. The population in this study were all employees of the Regional Secretariat of Bogor Regency with a total of 533 people. The sampling method using the 5% slovin formula yielded 229 samples, with the proportion of 107 civil servants and 122 contract workers. Primary data was obtained using a questionnaire with a scale of 1-5. The data analysis method uses the Partial Least Square method with the SmartPLS version 4 application. The results of the study are Leadership (X1) has a significant positive effect on Performance (Y) at the Regional Secretariat of Bogor Regency, Work Environment (X2) has no effect on Performance (Y) at the Regional Secretariat Bogor Regency, Organizational Culture (X3) has a negative effect on Performance (Y) at the Regional Secretariat of Bogor Regency, Leadership (X1) has a significant negative effect on Performance (Y) moderated by motivation (X4) at the Regional Secretariat of Bogor Regency, Work environment (X2) has an effect significant negative effect on performance (Y) moderated by motivation (X4) at the Regional Secretariat of Bogor Regency, Organizational Culture (X3) has a significant positive effect on performance (Y) moderated by motivation (X4) at the Regional Secretariat of Bogor Regency.